Principles of marketing - Kotler, Philip; Armstrong, Gary (Gary M.); Balasubramanian, Sridhar; Agnihotri, Parfulla Y. (Pearson ; Pearson India Education, 2023)
"The nineteenth edition of Principles of Marketing reflects the major trends and shifting forces that impact marketing in this digital age of customer value, engagement, and relationships"--